Анализ методов обработки сигналов систем радиоакустического зондирования атмосферы - Карташов, В. М.; Бабкин, С. И.; Пащенко, С. В.; Куля, Д. Н. (ХНУРЭ, 2011)
We consider the optimal scheme to achieve the most plausible estimates of the velocity the object – an acoustic wave packet, which is more in line with the scheme of estimation of the energy of the signal parameter.
Keywords: радиоакустическое зондирование; обработка сигналов; рассеяние радиосигнала